2011
DOI: 10.1111/j.1468-3083.2011.04109.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of sentinel node biopsy in patients with thick melanoma: a meta‐analysis

Abstract: The results of this analysis showed that thick melanoma patients with a positive SLN had a significantly worse survival compared with SLN negative patients, thus supporting the routine adoption of SLN biopsy as a prognostic tool also for this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…18 In contrast, multiple studies have demonstrated that the status of the sentinel lymph node is predictive of survival with node-negative patients having a 5-year survival of 56-71% versus 26-48% with node-positive disease. [30][31][32][33][34] In a recent metaanalysis by Rondelli et al, 35 and colleagues SNB status was predictive of survival with a 71% 5-year survival if node(s) was negative for disease and 39% if positive. 35 Our findings are similar with a 5-year DSS of 75.4% for negative sentinel node patients versus 44.1 % in node-positive patients (Fig). In addition, as new immunotherapy regimens for melanoma are studied in the adjuvant setting, the status of SNB may provide important information for patient selection.…”
Section: Discussionmentioning
confidence: 95%
“…18 In contrast, multiple studies have demonstrated that the status of the sentinel lymph node is predictive of survival with node-negative patients having a 5-year survival of 56-71% versus 26-48% with node-positive disease. [30][31][32][33][34] In a recent metaanalysis by Rondelli et al, 35 and colleagues SNB status was predictive of survival with a 71% 5-year survival if node(s) was negative for disease and 39% if positive. 35 Our findings are similar with a 5-year DSS of 75.4% for negative sentinel node patients versus 44.1 % in node-positive patients (Fig). In addition, as new immunotherapy regimens for melanoma are studied in the adjuvant setting, the status of SNB may provide important information for patient selection.…”
Section: Discussionmentioning
confidence: 95%
“…Age-related disparities in surgical management of primitive melanoma A significant proportion of patients with thick melanomas do not undergo lymph node staging with SLNB, despite the fact that it has been recommended by guidelines since 1998 and supported by retrospective and prospective institutional data [55][56][57][58][59][60][61][62][63][64][65] There are several possible explanations for this discrepancy. For example, multimorbidity could have precluded the use of SLNB in older patients.…”
mentioning
confidence: 99%
“…8,16 DFS was longer in patients with negative SNB, when compared with patients with positive SNB but there was no significant difference in terms of OS in the two groups. The impossibility to obtain significant differences in terms of OS can be explained by the morphology of the survival curves ("banana shaped" curves).…”
Section: Discussionmentioning
confidence: 85%